2023
DOI: 10.3389/fonc.2023.1250355
|View full text |Cite
|
Sign up to set email alerts
|

High serum miR-223-3p expression level predicts complete response and prolonged overall survival in multiple myeloma patients undergoing autologous hematopoietic stem cell transplantation

Damian Mikulski,
Mateusz Nowicki,
Izabela Dróźdż
et al.

Abstract: IntroductionAHSCT is the treatment of choice for newly diagnosed patients with transplant-eligible multiple myeloma (MM). However, considerable variability in response to autologous hematopoietic stem cell transplantation (AHSCT) results in only 50% of patients achieving complete response (CR) after AHSCT, which is directly associated with improved progression-free and overall survival (OS). In this study, we aimed to investigate the potential predictive role of selected serum miRNAs in MM patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Our previous study demonstrated that small non‐coding RNA molecules, miRNAs, are significantly deregulated in serum during the AHSCT procedure 17,18 . According to bioinformatic analysis, conducted using miRNet 2.0 (http://www.mirnet.ca/ accessed July 16 2023), we found that six significantly deregulated miRNAs are associated with the gene THBS1 encoding the protein thrombospondin‐1 (Figure 1A) (Figure S1).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Our previous study demonstrated that small non‐coding RNA molecules, miRNAs, are significantly deregulated in serum during the AHSCT procedure 17,18 . According to bioinformatic analysis, conducted using miRNet 2.0 (http://www.mirnet.ca/ accessed July 16 2023), we found that six significantly deregulated miRNAs are associated with the gene THBS1 encoding the protein thrombospondin‐1 (Figure 1A) (Figure S1).…”
Section: Methodsmentioning
confidence: 93%
“…Our previous study demonstrated that small non-coding RNA molecules, miRNAs, are significantly deregulated in serum during the AHSCT procedure. 17,18 According to bioinformatic analysis, conducted using miRNet 2.0 (http://www.mirnet.ca/ accessed July 16 2023), we found that six significantly deregulated miRNAs are associated with the gene THBS1 encoding the protein thrombospondin-1 (Figure 1A) (Figure S1). 19 Combined with literature analysis regarding various THBS-1 influences on the immune system we assumed THBS-1 serum concentration may act as a biomarker of infectious complications ocurrence.…”
Section: Selection Of Potential Protein Predictive For Infectious Com...mentioning
confidence: 99%
“…The focus on serum miRNAs stems from the clinical availability, reliability, and ease of introducing blood-based biomarker tests to clinical practice. Serum miRNAs, released into circulation by various cell types, including hematopoietic and non-hematopoietic cells, would thus provide a more comprehensive insight into the incipient complications and outcome predictions [49][50][51]. In addition, assessment of miR-122 in other populations, including allogeneic hematopoietic stem cell transplant recipients, would be exciting in the context of hepatic GvHD, as miR-122 was already reported to be up-regulated in sera of patients with chronic GvHD [52].…”
Section: Discussionmentioning
confidence: 99%